IMPLEMENTASI KEBIJAKAN PENINGKATAN PRESTASI ATLET PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR PADA DINAS PEMUDA DAN OLAHRAGA DAERAH PROVINSI SULAWESI TENGAH - Arifudin Arifudin (Katalogis, 2018)
This aims of this research the implementation of athletes performance improvement policy of Education and Training Center Students Sports at Department of Youth and Sports, Central Sulawesi of Edward III (1980:10)which covers; (1) Communication, (2) Resource, (3) Disposition, (4) Bureaucracy Structure.This research used qualitative approach with descriptive method. This research was carried out at the office of Education and Training Center Students Sports, Central Sulawesi with 7 (seven) informants chosen purposively.Techniques of the data collections are interviews, observations, and documentations. The data were analyzed by using Milles and Huberman Model (1992:20). The result of the research shows the implementation of athletes performance improvement policy of Education and Training Center Students Sports at Department of Youth and Sports, Central Sulawesi that (1) the communication to socialize the education center and the coaching of athletes achievement and the programs generally is categorized as good. (2) Human resource is already available both coaches, tutors and athletes, but there are still shortcomings that medical personnel, nor financial resources that still need attention from the government (3) Disposition: the admission of trainers and tutors which were recruited have the capability of imposed duties and responsibilities. (4) Bureaucracy Structure: On the right to implementing education and coaching the athletes are in accordance to SOP that has been specified by the Department of Youth and Sports, Central Sulawesi. It is concluded that of the four aspects that have been running quite well is the communication aspect, disposition and bureaucratic structure, while the aspect of resource has not run optimally, especially medical resources and sources of funding / budget.